Exploring the Implementation of Solar Energy in Higher Education Institutions in Malaysia - Mudzengi, Mayibongwe Tafara (2016)
The area of research aims, to explore the implementation of solar energy in Higher Educational Institutes (HEIs) in Malaysia, to evaluate the prospectus usage of solar energy and Government policies, incentives and increasing the implementation of renewable energy solutions as well research into institutions currently using Solar Energy, determining how the educational institutions and community could benefit from a solar array. Renewable energy is the key to a better world which needs to be adopted and embraced with uncluttered mind-set where the need of adoption of solar energy in Higher Educational Institutions (HEIs) in Malaysia and the present-day precipitous rise, global adoption of solar energy is well documented. Various types of institutions will be included in the research, Private, Government, and Semi Government to attain a broad spectrum on the energy needs in the Malaysia educational system. The research will adopt qualitative research methods as qualitative research methods will enable the researchers to understand people better based on what they say and what they do (Myers, 2013), which will have analysed and cross tabulation of the groups. The adoption study of a solar energy in HEIs could be substantially beneficial for all parties involved, administration, students, research and creating green environment, a comprehensive feasible analysis, recommendation with the developing some propositions, hence the adopting the focus group method as the research designs for the study to be rationale (Jennings 2009). A qualitative approach to the research involved 7 interviewees from two groups, the HEIs and professional expertise in solar energy. Based on the findings, solar energy is a favourable energy alternative to implement for HEIs in Malaysia. Establishing a good energy saving culture is the advocator of application of solar energy in HEIs in Malaysia.